Mobile microlearning with repeated short video access: Effects on vocational skill retention - Putu Sudira; Rochmad Novian Inderanata; Slamet Widodo; Wagiran Wagiran; Sendi Tiyas Aryani (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
This study examined whether mobile microlearning that enabled repeated access to short, SOP-anchored instructional videos improved vocational skill retention compared with conventional practice instruction. A quasi-experimental pretest–posttest–delayed posttest design was implemented with 80 undergraduate students in a practice-based course (experimental n = 40; control n = 40). The experimental group learned through segmented microlearning videos (2–6 minutes) aligned with procedural steps, safety checkpoints, and quality criteria, accessible via mobile devices for rewatching before and after workshop practice. The control group received conventional instruction through instructor demonstration and job-sheet guidance without structured video re-access. Data were collected using a validated SOP-aligned practical performance rubric, a procedural knowledge test, and an observation sheet documenting procedural errors and task completion time; perceived cognitive load was measured using a brief rating scale. Content validity was established through expert judgment and instrument refinement, and reliability was supported through inter-rater agreement for performance scoring and internal consistency for test and scale measures. Data were analyzed using descriptive statistics, Shapiro–Wilk normality tests, Levene’s homogeneity tests, and independent-samples t-tests to compare groups at pretest (baseline equivalence), posttest (immediate outcomes), and delayed posttest (retention outcomes). The results indicated that the experimental group achieved significantly higher delayed practical performance and procedural knowledge than the control group, with fewer procedural errors and faster completion time. These findings suggest that rewatchable SOP-based mobile microlearning can strengthen durable procedural competence in vocational practice settings. This study contributes empirical evidence to vocational education literature by demonstrating that structured, rewatchable SOP-based microlearning enhances durable procedural competence.